A Phenomenological Inquiry into Discipline Formation among Early Childhood Learners: Islamic Parenting Practices in a Pesantren Setting - Tarisa Fitri; Itryah Itryah (Utan Kayu Publishing, 2025)
Despite the growing prominence of Islamic parenting literature, few studies have empirically explored how consistent Islamic parenting is practiced and experienced in pesantren-based early childhood education settings. This study aims to fill this gap by systematically investigating the lived experiences of parents and teachers at PAUD Az-Zikro Islamic Boarding School in shaping young children's discipline through Islamic parenting principles. Using a qualitative phenomenological approach, data were collected from four key informants—including parents, teachers, and caregivers—via in-depth interviews, participant observation, and document analysis, with rigorous validation through member checking and triangulation. The results reveal that the formation of discipline in early childhood is fostered by four interconnected components: adult exemplary behavior, consistent alignment of home–school rules, habituation of worship and daily routines, and ongoing value internalization through gentle reminders. Indicators of discipline observed include independence, responsibility, voluntary obedience, time management, and self-awareness. The unique pesantren environment, characterized by strong value alignment and integrated religious-social routines, reinforces the effectiveness of these strategies, although challenges remain from media and peer influences. This study advances theoretical understanding and provides actionable insights for educators and policymakers seeking to implement holistic character education strategies in both Islamic and broader early childhood contexts.